HUBUNGAN PENDAPATAN DAN KETAHANAN PANGAN KELUARGA DENGAN KEJADIAN STUNTING PADA BALITA DI POSYANDU KELURAHAN CAKUNG BARAT - Tiara Amanda (2023)
Stunting is a condition in which children under the age of five experience growth and developmental failure. It is characterized by a length or height that is not appropriate for their age. The causes of stunting can be influenced by various factors, including indirect causes related to family food security and root causes associated with family income. This study aims to examine the relationship between family income, food security, and the incidence of stunting in toddlers at the Cakung Barat Subdistrict's Posyandu. The method in this study uses descriptive quantitative with a cross-sectional design. The sampling technique used was a saturated sample or total sampling, with 103 respondents aged between 24-59 months. Data collection was conducted in May 2023 by measuring height and filling out a questionnaire guided by the researcher. The analysis, using the chi square test, revealed a significant relationship between family income (p=0.021), family food security (p=0.005), and the incidence of stunting in toddlers aged 24-59 months at the Cakung Barat Subdistrict's Posyandu. In conclusion, this study highlights that family income and food security are factors contributing to stunting, emphasizing the need for urgent attention to reduce the prevalence of stunting.